2020
DOI: 10.1186/s12890-020-01261-0
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-425-5p enhances lung cancer growth via the PTEN/PI3K/AKT signaling axis

Abstract: Background: miRNAs regulate a multitude of cellular processes and their aberrant regulation is linked to human cancer. However, the role of miR-425-5p in lung cancer (LCa) is still largely unclear. Here, we explored the role of miR-425-5p during LCa tumorigenesis. Methods: Cell proliferation was evaluated by cell counting Kit-8 and colony formation assay. Western blot and realtime PCR were accordingly used to detect the relevant proteins, miRNA and gene expression. Luciferase reporter assays were used to illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…miRNAs are non-coding RNAs of approximately 20 nucleotides, which typically function by degrading the expression of their target genes [ 15 ]. Dysregulation of miRNAs has been regarded as a critical factor in cancer cell growth and apoptosis in cancers such as colon, ovarian, and lung cancer [ 16 – 18 ]. Both miR-490-3p and miR-490-5p are members of the miR-490 family, which participate in tumorigenesis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are non-coding RNAs of approximately 20 nucleotides, which typically function by degrading the expression of their target genes [ 15 ]. Dysregulation of miRNAs has been regarded as a critical factor in cancer cell growth and apoptosis in cancers such as colon, ovarian, and lung cancer [ 16 – 18 ]. Both miR-490-3p and miR-490-5p are members of the miR-490 family, which participate in tumorigenesis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have been confirmed to participate in post-transcriptional gene expression regulation, acting as oncogenes or tumor suppressors [ 30 , 31 ]. In addition, the evidence demonstrated that tumor cells exhibit increased intrinsic ROS stress due to increased metabolic activity and mitochondrial malfunction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, miR-425-5p promotes cell growth by target binding to the PTEN 3‘UTR [ 21 ]. In lung cancer, miR-425-5p overexpression is positively associated with poor prognosis and enhances the proliferation, migration, and invasion of cells [ 22 , 23 ]. In renal cell carcinoma, studies have shown that miR-425-5p is an oncogene in this cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 99%